T-2 Toxin—The Most Toxic Trichothecene Mycotoxin: Metabolism, Toxicity, and Decontamination Strategies - Edyta Janik (MDPI AG, 2021)
Among trichothecenes, T-2 toxin is the most toxic fungal secondary metabolite produced by different Fusarium species. Moreover, T-2 is the most common cause of poisoning that results from the consumption of contaminated cereal-based food and feed reported among humans and animals. The food and feed most contaminated with T-2 toxin is made from wheat, barley, rye, oats, and maize. After exposition or ingestion, T-2 is immediately absorbed from the alimentary tract or through the respiratory mucosal membranes and transported to the liver as a primary organ responsible for toxin's metabolism. Depending on the age, way of exposure, and dosage, intoxication manifests by vomiting, feed refusal, stomach necrosis, and skin irritation, which is rarely observed in case of mycotoxins intoxication. In order to eliminate T-2 toxin, various decontamination techniques have been found to mitigate the concentration of T-2 toxin in agricultural commodities. However, it is believed that 100% degradation of this toxin could be not possible. In this review, T-2 toxin toxicity, metabolism, and decontamination strategies are presented and discussed.